2006
DOI: 10.1210/en.2005-0695
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hypothalamic Corticotropin-Releasing Hormone, Neuropeptide Y, and Proopiomelanocortin Gene Expression during Chronic Rapid Eye Movement Sleep Deprivation of Rats

Abstract: Chronic rapid eye movement (paradoxical) sleep deprivation (REM-SD) of rats leads to two conspicuous pathologies: hyperphagia coincident with body weight loss, prompted by elevated metabolism. Our goals were to test the hypotheses that 1) as a stressor, REM-SD would increase CRH gene expression in the hypothalamus and that 2) to account for hyperphagia, hypothalamic gene expression of the orexigen neuropeptide Y (NPY) would increase, but expression of the anorexigen proopiomelanocortin (POMC) would decrease. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 95 publications
9
71
0
1
Order By: Relevance
“…Nonetheless the measure does indicate an increase in available antigen that is most simply explained by an increase in content. During the chronic stress of sleep deprivation, an increase in CRH immunoreactivity in the PVH parallels the upregulation of CRH mRNA (Koban et al, 2006). Furthermore, our finding that plasma ACTH and adrenal hypertrophy relate positively to the neuronal intensity of CRHstaining in the PVH is consistent with an upregulation of CRH as reported in other models of chronic stress (Brown and Sawchenko, 1997;Makino, et al, 1995).…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless the measure does indicate an increase in available antigen that is most simply explained by an increase in content. During the chronic stress of sleep deprivation, an increase in CRH immunoreactivity in the PVH parallels the upregulation of CRH mRNA (Koban et al, 2006). Furthermore, our finding that plasma ACTH and adrenal hypertrophy relate positively to the neuronal intensity of CRHstaining in the PVH is consistent with an upregulation of CRH as reported in other models of chronic stress (Brown and Sawchenko, 1997;Makino, et al, 1995).…”
Section: Discussionsupporting
confidence: 90%
“…The present results confirm prior work indicating that sleep loss in rodents engenders an endocrinological profile consistent with negative energy balance, in which rats lose weight and peripheral fat mass, and leptin levels decline along with concordant changes in feeding-regulatory peptide systems of the medial basal hypothalamus (Barf et al, 2012;Koban and Swinson, 2005;Koban et al, 2006;Newman et al, 2009;Rechtschaffen and Bergmann, 1995). In this sense, transcriptional changes in arcuate nucleus NPY and CART were not qualitatively different in sleep loss vs food restriction.…”
Section: Comparing the Effects Of Sleep Deprivation And Food Deprivationsupporting
confidence: 90%
“…There is much interest in identifying the physiological basis of these behavioral changes, and studies to date have focused mainly on peripheral endocrine systems (eg, leptin and ghrelin) that regulate feeding in conjunction with energy-balance fluctuations. In some human studies, leptin and ghrelin levels are altered in sleep loss in directions that promote food intake, and rodent studies have shown that sleep curtailment modulates hypothalamic peptides and other systems whose activity tracks these circulating hormones (Barf et al, 2012;Koban et al, 2006;Martins et al, 2010;Spiegel et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…During a 20-day period of REM sleep loss, rats developed hyperphagia, increased metabolic rate (i.e. elevated uncoupling protein-1 expression in brown adipose tissue), and decreased leptin levels accompanied by upregulated mRNA expression of neuropeptide-Y (NPY), an orexigenic neuropeptide, and downregulated mRNA expression of pro-opiomelanocortin (POMC), an anorectic neuropeptide, in the hypothalamus [22,23]. Even a short period of sleep deprivation for 5 h by gentle handling increased feeding while decreasing leptin and increasing ghrelin concentrations in rats [24].…”
Section: Animal Laboratory Studiesmentioning
confidence: 99%